Analisa Pengaruh Penambahan Unsur Cu (Tembaga) Terhadap Sifat Mekanis Al – Si Melalui Proses Casting - Samhuddin; Al Ichlas Imran (Program Pendidikan Vokasi Teknik Mesin, 2021)
The purpose of this study is to determine the effect of the elements copper (Cu) on the mechanical properties of aluminum silicon (Al-Si). The mechanical properties of aluminum are lightweight, low temperature, corrosion resistance, mechanical properties vary (strength, hardness and ductility), good formability, and capable of a good cast. While the mechanical properties of copper are formability, good electrical conductivity, good thermal conductivity, good corrosion resistance, has a density of 8.93 g / cm³, the modulus of elasticity of 115 GPa and liquid temperature 1083 ° C. Materials used were Al-Si and the element copper alloy. The addition of the element copper (Cu) amounting to, 2%, 4%, 6% and 8%. Manufacturing of specimens with sand casting process. Mechanical testing were hardness and impact. In this study get the biggest hardness value alloy Al - Si addressed by the addition of Cu 0% or without alloy of 96.53 Kg / mm2, while the lowest hardness value of alloy Al - Si indicated by the addition of 2% Cu at 63.74 Kg / mm² , The strength values impack alloy Al - Si addressed by the addition of 8% Cu 0.026 J / mm2, while the value of impact strength low alloy Al - Si Cu indicated by the addition of 6% of 0,018 J / mm².